Soil-borne phytopathogen and bacterial biocontrol agents using mining tools. The pathosystem phytophthora sp-Olea europea - Bacillus sp. - Rossi, Maria Sol (2010)
Beneficial (e.g. biocontrol mycorrhizal and rhizobial symbioses, nutrient transformation and uptake) and harmful (e.g. phytopathogens, inorganic, phytoxicity, nutrient immobilization (climate change induced stress) interaction and their manipulation are of great topical interest. Phitophthora is a soil-borne pathogen against a great plant host number. We aimed phytophthora pathogen of Olea europaea. Using data mining tools we obtained information from large data bases as EML (Europe); DJJB (Japan) and GenBank (USA). Internal transcripted spacer (IGS) are regions of the DNA used to study taxonomic information in eucariota organisms because of this they are highly conserved in the evolution. Ribosomal 165 DNA was used to obtain taxonomic information about biocontrol bacteria. In our we looking for the relation ship between a large number of Phitophhora IBS and ITS sequences deposited into larges databases and the type and place of plant infected. We obtained information about the relationship that exidst between pathogenicity related to geographical point respect to pathosistem Phithothora sp against Olea europaea L. among unsupervised learning hierarchicqal clustering we obtained a clssification from ITS and IGS sequences.